1992
DOI: 10.1523/jneurosci.12-08-03187.1992
|View full text |Cite
|
Sign up to set email alerts
|

Sulforhodamine labeling of neural circuits engaged in motor pattern generation in the in vitro turtle brainstem-cerebellum

Abstract: A fluorescent molecular probe was used in combination with a novel in vitro preparation to study spatial patterns of neural activity associated with motor pattern generation. The in vitro brainstem-cerebellum preparation takes advantage of the turtle's unusual resistance to anoxia to preserve the entire neural network that connects the cerebellum, red nucleus, and reticular formation. This preparation was bathed in a 0.01% solution of sulforhodamine while it was activated unilaterally by electrical stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Several past studies suggest that SR 101, a charged fluorescent molecule, is taken up by endocytosis in synaptically activated neurons (Lichtman et al, 1985;Betz et al, 1992;Keifer et al, 1992;Teng et al, 1999;Anderson, 2001). The ultrastructural studies of muscle spindles in mammals and birds have shown the direct continuity of the perineurium of the entering nerve with the muscle spindles, which consist of collagen (Patten and Ovalle, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Several past studies suggest that SR 101, a charged fluorescent molecule, is taken up by endocytosis in synaptically activated neurons (Lichtman et al, 1985;Betz et al, 1992;Keifer et al, 1992;Teng et al, 1999;Anderson, 2001). The ultrastructural studies of muscle spindles in mammals and birds have shown the direct continuity of the perineurium of the entering nerve with the muscle spindles, which consist of collagen (Patten and Ovalle, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Sulforhodamine 101 was used for studying the activitydependent uptake of the probe in motor endplates (Lichtman et al, 1985) and in a turtle brainstem-cerebellum preparation (Keifer et al, 1992). The studies are all based on the ability of the dye to pass across the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Are reactive astrocytes that typically show reduced gap junction coupling (Xu et al 2009) also labeled by SR101? How can the differences in SR101 staining between rodent cortex and other central nervous system regions or species be reconciled (Keifer et al 1992;Ehinger et al 1994;Lavallee and Pflieger 2009)? Independent of the answers to these questions, SR101 has already proven and will continue to be a valuable tool in the study of astrocyte structure and function in the intact rodent brain and for a number of in vivo applications.…”
Section: Advantages and Limitations Of Sr101mentioning
confidence: 99%